High-voltage synthetic inductor for vibration damping in resonant piezoelectric shunt. (September 2021) - Dekemele, Kevin; Van Torre, Patrick; Loccufier, Mia
Resonant piezoelectric shunts are a well-established way to reduce vibrations of mechanical systems suffering from resonant condition. The vibration energy is transferred to the electrical domain through the bonded piezoelectric material where it is dissipated in the shunt. Typically, electrical and mechanical resonance frequencies are several orders apart. As such, finding a suitable high inductance component for the resonant shunt is not feasible. Therefore, these high inductance values are mimicked through synthetic impedances, consisting of operational amplifiers and passive components. A downside of these synthetic impedances is that standard operational amplifiers can only handle up to 30 V peak to peak and the state-of-the-art amplifiers up to 100 Vpp. However, as mechanical structures tend to become lighter and more flexible, the order induced voltages over the piezoelectric material electrode voltages increase above these limitations. In this research, a high-voltage synthetic inductor is proposed and built by combining the bridge amplifier configuration and the output voltage boost configuration around a single operational amplifier gyrator circuit, effectively quadrupling the range of the synthetic inductor to 400 Vpp. The impedance of the circuit over a frequency range is numerically and experimentally investigated. The synthetic inductor is then connected to a piezoelectric material bonded to a cantilever beam. Numerical and experimental investigation confirms the high-voltage operation of the implemented circuit and its suitability as a vibration damping circuit.